Specific Targeting of Caspase-9/PP2A Interaction as Potential New Anti-Cancer Therapy - Arrouss, Issam; Nemati, Fariba; Roncal, Fernando; Wislez, Marie; Dorgham, Karim; Vallerand, David; Rabbe, Nathalie; Karboul, Narjesse; Carlotti, Françoise; Bravo, Jeronimo; Mazier, Dominique; Decaudin, Didier; et al. (PLOS ONE, 2013)
Purpose PP2A is a serine/threonine phosphatase critical to physiological processes, including apoptosis. Cell penetrating peptides are molecules that can translocate into cells without causing membrane damage. Our goal was to develop cell-penetrating fusion peptides specifically designed to disrupt the caspase-9/PP2A interaction and evaluate their therapeutic potential in vitro and in vivo. Experimental Design We generated a peptide containing a penetrating sequence associated to the interaction motif between human caspase-9 and PP2A (DPT-C9h), in order to target their association. Using tumour cell lines, primary human cells and primary human breast cancer (BC) xenografts, we investigated the capacity of DPT-C9h to provoke apoptosis in vitro and inhibition of tumour growth (TGI) in vivo. DPT-C9h was intraperitonealy administered at doses from 1 to 25 mg/kg/day for 5 weeks. Relative Tumour Volume (RTV) was calculated. Results We demonstrated that DPT-C9h specifically target caspase-9/PP2A interaction in vitro and in vivo and induced caspase-9-dependent apoptosis in cancer cell lines. DPT-C9h also induced significant TGI in BC xenografts models. The mouse-specific peptide DPT-C9 also induced TGI in lung (K-Ras model) and breast cancer (PyMT) models. DPT-C9h has a specific effect on transformed B cells isolated from chronic lymphocytic leukemia patients without any effect on primary healthy cells. Finally, neither toxicity nor immunogenic responses were observed. Conclusion Using the cell-penetrating peptides blocking caspase-9/PP2A interactions, we have demonstrated that DPT-C9h had a strong therapeutic effect in vitro and in vivo in mouse models of tumour progression.